Edukasi Pencegahan dan Tatalaksana Awal Infeksi Saluran Pernapasan Akut pada Anak - Marhaeni Hasan; Fera The; Kiky Frederik Rompis (Jurnal Surya Masyarakat, 2023)
Acute Respiratory Infection (ARI) is an infection that can occur in the respiratory tract. The World Health Organization (WHO) in 2015 stated that, ARI is the leading cause of death in children less than 5 years old in the world. This service aims to improve the degree of public health knowledge through counseling on the importance of prevention and early management of ARI in children. This method of service is to conduct an initial survey of the location of the service, conduct counseling related to the initial management and prevention of ARI in children accompanied by discussions at the Gambesi Health Center. The target of this devotion is mothers who have toddler children.  The result obtained is that there is an increase in maternal knowledge before and after counseling is carried out